(untitled) (Journal of EAHIL, 2021)
During COVID-19 pandemic Electronic Library of Medicine – Jordan (ELM) was on the upfront of dealing with the crisis. ELM worked on a response plan for the Digital Transformation of its online services with focus on COVID-19. The plan strategy consisted of four phases: preparation, implementation, evaluation and sustainability. The immediate management for COVID-19 pandemic was done through having a dedicated COVID-19 Knowledge Center and digitizing all training and educational sessions. An online survey for the evaluation of the impact on the Digital Transformation of library services was done. Evaluation results showed satisfactory impact. The COVID-19 pandemic was an opportunity to ELM, and it even enhanced the library services and training. Challenges concerning sustainability and accreditation of the continuing professional development need to be addressed with concerned authoritative parties within Jordan.